Estimating efficiency of Directive 2011/24/EU cross-border healthcare in member states - Ibrahim, Mustapha D.; Hocaoglu, Mevhibe B.; Numan, Berna; Daneshvar, Sahand (Becaris Publishing, 2018)
Aim: Directive 2011/24/EU on patients' rights in cross-border healthcare facilitates EU citizens' access to and reimbursement for healthcare provided or prescribed in a member state other than the member state of affiliation. Materials & methods: The efficiency of cross-border healthcare policy is evaluated using data envelopment analysis of relevant items in Eurobarometer Survey on Safety and Quality of Care and Patients' Rights in the EU. Results: Our study shows policy inefficiency in 52% of the 25 EU member states included in the analysis. Addressing difficulties patients encounter while seeking reimbursement from their national health service or health insurer and reducing the number of adverse events patients experience when receiving healthcare improves policy efficiency. Conclusion: Our findings confirm that there is country-level variation in cross-border healthcare policy efficiency.
Keywords: cross-border healthcare directive; data envelopment analysis; efficiency; eurobarometer; European Union; health policy